Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm trying to find out all $z \in C$ that satisfy the following condition:

$|z+1|+|z-i|=3$

I understand that $|z|=r$ represents a circle with a radius of $r$. I also understand that $|z+1|=r$ can be written as $|(x+1)+yi|=\sqrt{(x+1)^2+y^2}=r$ which can then be squared to get $(x+1)^2+y^2=r^2$ which represents the circle with a radius of r, with center in $(-1,0)$.

So, back to my problem:

Unlike the example with $|z+1|=r$, where it is easy to square the equation, squaring $|z+1|+|z-i|=3$ written as $\sqrt{(x+1)^2+y^2}+\sqrt{x^2+(y-1)^2}=3$ equals:

$(x+1)^2+(y-1)^2+x^2+y^2+2\sqrt{(x+1)^2+y^2}\sqrt{x^2+(y-1)^2}=9$ which is a nightmare to solve, if at all possible.

I am sure there must be some elegant way to solve this kind of problem. The way I'm thinking is this:

$|z+1|$ by itself seems to represent a circle centered at $(-1,0)$, with an undefined radius, and $|z-i|$ seems to represent a circle centered at $(0,1)$, also with an undefined radius. However, the sum of those two radii must be 3. But I can't seem to wrap my mind around what this would represent (when drawn on Cartesian plane), or how to solve it analytically. So, how would one approach this problem? Even a hint would (probably) suffice.

share|improve this question
1  
This question seems related: Plot $|z - i| + |z + i| = 16$ on the complex plane –  Martin Sleziak Oct 9 '12 at 10:50
1  
I am sorry. I really did search before posting. But this Q did not appear in first 50-ish of results. Thanks for linking. –  Kornelije Petak Oct 9 '12 at 10:52
add comment

2 Answers 2

up vote 1 down vote accepted

Let $\sqrt{(x-a)^2+(y-b)^2}+\sqrt{(x-c)^2+(y-d)^2}=e$

$\sqrt{(x-a)^2+(y-b)^2}=e-\sqrt{(x-c)^2+(y-d)^2}$

Squaring we get, $(x-a)^2+(y-b)^2=e^2+(x-c)^2+(y-d)^2-2e\sqrt{(x-c)^2+(y-d)^2}$

or, $2e\sqrt{(x-c)^2+(y-d)^2}=e^2+(x-c)^2-(x-a)^2+(y-d)^2-(y-b)^2$

or, $2e\sqrt{(x-c)^2+(y-d)^2}=e^2+(2x-c-a)(a-c)+(2y-d-b)(b-d)$

or, $e\sqrt{(x-c)^2+(y-d)^2}=x(a-c)+y(b-d)+f$ where $2f=e^2-(c+a)(a-c)-(d+b)(b-d)$

Squaring we get, $e^2((x-c)^2+(y-d)^2)=(x(a-c)+y(b-d)+f)^2$

$\implies x^2(e^2-(a-c)^2)-2xy(a-c)(b-d)+y^2(e^2-(b-d)^2)-2x(e^2c+f(a-c))-2y(e^2d+f(b-d))+e^2(c^2+d^2)-f^2=0$

Using this, $4(a-c)^2(b-d)^2-4(e^2-(a-c)^2)(e^2-(b-d)^2)$

$=4e^2((a-c)^2+(b-d)^2-e^2)$

Now $e=\sqrt{(x-a)^2+(y-b)^2}+\sqrt{(x-c)^2+(y-d)^2}$ $=|(x,y)-(a,b)|+|(x,y)-(c,d)|<|(a,b)-(c,d)|$

So, $(a-c)^2+(b-d)^2-e^2<0$, so the locus of $(x,y)$ is an ellipse ,but not a circle unless the coefficient of $xy$ is $0$.


Alternatively,

$\sqrt{(x+1)^2+y^2}+\sqrt{x^2+(y-1)^2}=3$

$\sqrt{(x+1)^2+y^2}=3-\sqrt{x^2+(y-1)^2}$

Squaring we get, $ (x+1)^2+y^2=9+x^2+(y-1)^2-6\sqrt{x^2+(y-1)^2}$

$2x+2y-8=-6\sqrt{x^2+(y-1)^2}$

$x+y-4=-3\sqrt{x^2+(y-1)^2}$

Squaring we get, $(x+y-4)^2=9(x^2+(y-1)^2)$

$8x^2-2xy+8y^2+8x-10y-7=0$

Using this or this, $(-2)^2-4\cdot 8 \cdot 8<0$

So, the curve is an ellipse.

Using this , we can remove $xy$ terms.

share|improve this answer
add comment

$|z+1|$ is the distance from the point $z$ to the point $-1$, and $|z-i|$ is the distance from $z$ to the point $i$. Thus, you’re looking at the set of all points $z$ such the sum of the distances from $z$ to $-1$ and $i$ is $3$. Which conic section is defined as the locus of points $P$ such that the sum of $|PA|$ and $|PB|$ is a constant for two fixed points $A$ and $B$?

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.